Электромагнитные методы и приборы для контроля металлургических изделий - Ощепков Павел Кондратьевич (1969)
Экземпляры: КХ (20171020) / Инвентарный номер: 486481 / Сис.шифр: 620.1 / Авт.знак: И 73 / ГРНТИ: 81 / ББК: 3